Chemiluminescent Measurement of Telomere DNA Content in Biopsies - Colleen A. Fordyce; Christopher M. Heaphy; Jeffrey K. Griffith (BioTechniques)
Telomeres are nucleoprotein complexes that protect the ends of chromosomes from fusion and degradation. They are typically shorter in tumor cells than in paired normal cells, and shorter telomeres are associated with poor outcome in cancer. We previously described a slot blot-based method for measuring telomere DNA content, a proxy for telomere length. Although this method represented an improvement over existing methods, its 30-ng limit of sensitivity was insufficient for use with biopsy or other scant tissues. Here we describe a chemiluminescent slot blot assay for telomere DNA content that has the sensitivity required for use with biopsy materials. The results obtained with DNA derived from human placental, HeLa, human peripheral blood lymphocytes, sham-needle core prostate biopsies, and archival prostatectomy tissues demonstrated that telomere DNA content can be reliably and reproducibly measured in 5 ng, and sometimes as little as 2 ng, genomic DNA. Sham-needle core prostate biopsy and prostatectomy specimens processed in parallel produced comparable results. The contribution of truncated telomeres in admixtures containing as much as 75% normal placental DNA could be established. We also demonstrated that the treatment of tissue with formalin before DNA purification does not decrease the efficacy of the assay.